Path Dependency or Route Flexibility in Demand Responsive Transport? The Case Study of TWIST project - Erdősi, Ferenc; Gál, Zoltán; Gipp, Christoph; Varjú, Viktor (Discussion Papers, 2012)
TWIST (Transport with a Social Target) is a European part-financed project by INTERREG III B - CADSES. It oriented towards the promotion of the mo¬bility in underprivileged areas by experimenting a Demand Responsive System (DRT). Various European countries participated in the project and implemented the pilot system. The project is inspired by the cohesion policies of the EU which aim for territorial integration of countries or regions of countries which are structurally less developed. Areas participating show a lack of balance in infra¬structural and transport services in mountain, rural and suburban areas. The implementation of a DRT system aimed to reduce the social and eco¬nomic gap between rural/mountainous and urban areas, and aimed to set up an appropri¬ate model to solve the problems in areas with similar background offering the possibility for greater mobility to the weakest part of the population, such as the elderly or disabled people, women, children and others who have no own cars. Experience from the research results suggest that for financial and scheduling reasons DRT services do not aim to be dominant public transport providers in a market, but are regarded as vital suppliers of services where conventional solutions are untenable, for example low demand areas, special transport ser¬vices and where social exclusion is evident with low number of potential sub¬sidy. Old-aged people, disabled social groups and individuals without cars may have extreme significance in servicing transport demands within the framework of DRT systems. As the research shows, the more regulated the legal envi¬ronment, the less conflict there is between DRT and other public transport modes. It seems in terms of technologies for DRT services, the level of telematics support available at the local level too. Intermodality needs an adequate environment. Some fixed stops are needed by all means for interconnections. Services need fixed starting time and a definite starting point for departure. Completely circular schemed flexible routes very rarely prove to be viable in the long run. One of the most serious problems is the unclear juridical status and regulation of the governance of DRT systems. Their financial system with the charging mechanism is rather chaotic and hectic (too many subjective elements are built into the system) and the degree and efficiency of their subsidization system also leaves several question marks especially.